Mekanisme Pengenaan Pajak Air Tanah oleh Badan Pendapatan Daerah Kabupaten Malang - Cinta Mazaya Quincy Affandi (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Groundwater tax is a type of local tax levied by regency/city that has the potential to support regional revenue while also controlling excessive groundwater use, which can have a negative impact on the environment. Groundwater tax is levied on the extraction and/or use of groundwater by individuals and entities, as determined by the regional government, and is collected using an official assessment system. The local government referred to is the regency/city local government that has authority in the field of local revenue management, one of which is the Malang District Revenue Agency. The purpose of this fieldwork is to identify and understand the mechanism of imposing Groundwater Tax at the Malang Regency Regional Revenue Agency. The methods used in preparing this Final Project Report are qualitative and quantitative methods with data collection techniques in the form of observation, interviews, and documentation studies. The data used consists of primary data obtained through interviews and direct observation during the Field Work Practice, as well as secondary data in the form of literature, legislation, and documents related to Groundwater Tax. The findings of the observation indicate that the mechanism for levying Groundwater Tax begins with the registration of local taxpayers and taxable objects, the completion of the Tax Object Notification Form by the Sub-district Technical Implementation Unit, followed by on-site verification by assessment staff to ensure that the data reflects actual conditions, thereby serving as the basis for determining the tax due. The Tax Object Notification Letter is verified after data adjustments and the calculation of the tax due have been carried out by the system. The calculation is based on water consumption volume and uses rates according to business group classification. In the event of changes to data, such as a change in business group, a correction to the Local Tax Assessment Letter may be made, resulting in an adjustment to the calculation of the tax due in line with the actual conditions.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Local Tax; Groundwater Tax; Tax Imposition Mechanism; Malang District Revenue Agency